Revision of the mining bee subgenus Andrena (Longandrena) (Hymenoptera: Apoidea: Andrenidae) - Radchenko, Vladimir G.; Allahverdi, Mohammad; Fekrat, Lida (Zootaxa, 2021)
All three hitherto described species of the Palearctic subgenus Andrena (Longandrena Osytshnjuk, 1993), are revised and redescribed. This subgenus is characterized by an unusually long glossa, a rare character among short-tongued bees. A revised diagnosis of this subgenus is given. A key to the species of A. (Longandrena) is provided, and all diagnostic morphological features are illustrated in detail. The Central Asian species Andrena longiceps Morawitz 1895 is recorded for the first time from Iran. The distribution map of the subgenus is also presented.